Optimum Nitrogen and Density Allocation for Trade−Off Between Yield and Lodging Resistance of Winter Wheat - Haitao Liu; Shufang Sun; Min Jin; Chunhui Li; Jiayu Wang; Haixing Cui; Yong Li; Zhenlin Wang (Agronomy)
Increasing nitrogen and planting density can enhance crop yield, but it can reduce lodging resistance due to decreased lignin content. There is an urgent need to find feasible measures to balance these conflicting factors. We conducted a two-year field experiment in Tai’an, Shandong Province, China, evaluated SN23 (lodging resistant) and SN16 (lodging sensitive), under three nitrogen applications (120 kg/ha, N1; 240 kg/ha, N2; 360 kg/ha, N3) and four planting densities (75 plants/m2, D1; 225 plants/m2, D2; 375 plants/m2, D3; 525 plants/m2, D4), with N2D2 as the control, and measured lodging resistance related indexes and yield. N2D3 (SN23) increased internode length by 0.40 cm, reduced fresh weight by 0.09 g, resulting in a bending moment reduction of 0.39 g/cm. Lignin, cellulose, and hemicellulose decreased by 18.27, 16.48, and 16.22 mg/g DW, while S and G lignin subunits decreased by 118.09 and 127.34 μg/g DW, and H subunit increased by 23.59 μg/g DW. Eventually, the breaking strength was reduced by 1.74 g/cm resulting in a reduction of 0.09 in the lodging resistance index. The yield reached 10.17 t/ha due to an increase in spike number by 100.33 plants/m2, achieving an optimal balance between yield and lodging resistance in this experiment. This study provides a viable solution for balancing lodging resistance and yield in winter wheat.